With so many different techniques for lung nodule localization, the time has come for randomization - Weksler, Benny (Video-Assisted Thoracic Surgery; Vol 2 (August 2017): Video-Assisted Thoracic Surgery, 2017)
I read with interest the review manuscript by Yoshida and Nakajima on the preoperative localization of lung nodules for minimally invasive resection. Many methods have been described for localization and those can be divided into two broad categories: (I) localization by computed tomography; (II) localization by endobronchial means. Different agents are used by with each technique.